Kazakhstan—Macroeconomic Policy. Developments, Challenges and Opportunities - Horton, Mark A. (My University, 2017)
Kazakhstan—Macroeconomic Policy. Developments, Challenges and Opportunities
Keywords: Macroeconomics; Kazakhstan; economic development